The Influences Of Education, Training, Personality, And Work Period On The Competence Of Employees At The Regional Development Planning Agency Of Pagar Alam City - Mahyidin, Muhammad; Hardiyansyah, Hardiyansyah; Aprini , Nisma (Journal of Indonesian Management, 2023)
This study aims to determine and analyze the effect of Education, Training, Personality, and Years of Service on the Competence of employees at the Regional Development Planning Board of Pagar Alam City. This study uses quantitative research methods with respondents, namely employees of the Regional Development Planning Board of Pagar Alam City, totaling 41 respondents. Tests in this study used multiple linear regression analysis with the tools of the SPSS (Special Package and Service Solution) version 26 program. The results of the research show that Education, Training, Personality, and Years of Service have proven to have a significant effect on the competence of employees at the Regional Development Planning Board of Pagar Alam City, both partially and simultaneously